Schemas for induction. (August 2020) - Baker, Alan
Highlights: Schemas for induction can be useful even if they have exceptions. There are important analogies between schemas for induction and schemas for invalid deductive arguments. Schemas can play an explanatory role in analyzing inductive reasoning.